The employment of Grab riders with physical disabilities in e-hailing services: challenges and coping strategies - Wan Abdullah, Wan Arnidawati; Zulkarnain, Nur Sofea Qistina (The Malaysian Psychological Association, 2024)
E-hailing services, such as Grab, has become increasingly prevalent in recent years. However, little is known about the participation of individuals with physical disabilities in this service sector. This study explores the lived experience of Grab riders with physical disabilities and their ability to cope with the challenges working as Grab riders. A qualitative research approach using Interpretative Phenomenological Analysis (IPA) was adopted. Semi-structured interviews with three grab riders with physical disabilities in Klang Valley were employed for data collection and the data obtained were analysed thematically. Challenges highlighted include Grab job application process, movement and mobility limitations, weather conditions and customers’ attitude. Various coping strategies were employed to overcome these challenges such as resilience and determination, support from family and friends, comfortable locations and areas, and overcoming misconceptions. This research provides a platform for the voices of Grab riders with physical disabilities to be heard. The findings can contribute better understanding about Grab riders with physical disabilities and discover valuable perspectives in the development of relevant policies for persons with disabilities in Malaysia to support the employment and well-being of individuals with physical disabilities in the e-hailing industry.